The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/etc.2428
|View full text |Cite
|
Sign up to set email alerts
|

A molecular method for assessing the effects of potential contaminants on the rate of zebrafish (Danio rerio) development

Abstract: Monitoring expression of the developmentally regulated genes shh, sox2, and tnnt1 by reverse transcriptase polymerase chain reaction (RT-PCR) allows determination of the rate of embryogenesis in zebrafish (Danio rerio) embryos without direct visual observation. The utility of combining this approach and morphological methods during toxicity studies was demonstrated with embryos developing at either 28.5 °C or 24.5 °C and with embryos exposed to sublethal doses of silver nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The inclusion of molecular endpoints in toxicity testing methods that utilize early–life stage fishes has been advocated for previously . In the present study, we sought to determine whether zebrafish and fathead minnows from the FET and LGS tests experienced alterations in the expression of genes related to growth ( igf1 and igf2 ) and toxicity ( hsp70 , cyp1A , glulb ).…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of molecular endpoints in toxicity testing methods that utilize early–life stage fishes has been advocated for previously . In the present study, we sought to determine whether zebrafish and fathead minnows from the FET and LGS tests experienced alterations in the expression of genes related to growth ( igf1 and igf2 ) and toxicity ( hsp70 , cyp1A , glulb ).…”
Section: Discussionmentioning
confidence: 99%
“…By so doing, we were able to observe an increase in sensitivity of >30%. Other studies have reported relevant increases in sensitivity after addition of molecular (Hermsen et al ; Beasley et al ; Jeffries et al ), morphological (Lammer et al ; Brannen et al ; Di Paolo et al ), and behavioral endpoints to the FET (Di Paolo et al ), and thus this could be a fruitful solution to the problem of overcoming OECD 236 sensitivity issues. In addition to comparing LC50 values across fish tests for a specific effluent, we have shown ways to improve the sensitivity of the FET without extra costs or administrative burdens.…”
Section: Discussionmentioning
confidence: 95%